English or ELFish? A teaching dilemma of the 21st century - Dziubalska-Kołaczyk, Katarzyna (In: Migdał, Jolanta and Agnieszka Piotrowska-Wojaczyk (eds.) Cum reverentia, gratia, amicitia… Księga jubileuszowa dedykowana Profesorowi Bogdanowi Walczakowi. Poznań: Wydawnictwo Rys, 2013)
Contrary to the predictions of Jan Baudouin de Courtenay(1908), English has become the international auxiliary language worldwide. Not artificial Esperanto, but natural English. Globalization of a natural language, however, inevitably hasconsequences for the language itself. How English is International English, we may ask. For linguists, this is a question of language change. For teachers, this is a matter of choice between a full-fledged native version of the language vs. the so -called ELF (English as a Lingua Franca, cf. the discussion in Dziubalska -Kołaczyk and Przedlacka 2008). The aim of this paper will be to arrive at a moderate “recipe” for teachers and learners.